Improving methodological solutions to increase the efficiency and quality of outsourcing services - Navruz-Zoda Bakhtiyor Neg matovich; Nasiba Ergasheva (THE INNOVATION ECONOMY, 2026)
This article analyzes methodological solutions for improving the efficiency and quality of outsourcing services, including the goals and objectives of outsourcing services, the choice of the outsourcing services market by the client, the identification of important features and characteristics of preschool educational organizations and their classification, the presentation of outsourcing in preschool educational organizations as a set of processes, and scientifically based proposals and recommendations for the classification of individual processes in this service and their important features are presented